Literary Cross-Pollination between Hassaniya and Arabic: The Influence of Hassaniya Literature on the Moroccan Literary Scene - Aboubker, Taoufik (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2026)
Hassaniya literature constitutes an intrinsic component of Moroccan cultural heritage, reflecting the desert environment with its distinctive values and traditions and characterized by its predominantly oral nature as well as its rich linguistic and stylistic legacy. Moroccan literature, by contrast, in its diverse written expressions, represents a dynamic confluence of linguistic and cultural influences, providing fertile ground for interaction with various literary forms, foremost among them Hassaniya literature. Employing a historical-analytical approach, this study examines the dynamics of interaction between Hassaniya and Moroccan literatures by analyzing the influence of Hassaniya literary production on the broader Moroccan literary scene and highlighting its contribution to enriching the national literary field through the works of Saharan poets and writers. This interaction has been shaped by several factors, notably the role of zawiyas, scholarly institutions, and Saharan families in disseminating desert literary traditions, particularly the family of Sheikh Ma al-Ainin. The study further explores thematic intersections between the two literatures within the Saharan environment in relation to national identity, including resistance, religion, and language. Hassaniya literature expresses key dimensions of Moroccan social identity and embodies its values through distinctive poetic and narrative forms, intersecting with Moroccan literature in documenting questions of belonging and identity. Ultimately, the paper demonstrates how the plurality of Morocco’s cultural currents and social components has historically functioned—and continues to function—as a source of cohesion and strength, enriching national unity through literary interaction and integration between Hassaniya and Moroccan literatures in a deeply rooted and mutually reinforcing relationship.